PERAN GURU BIOLOGI DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN LINTAS MINAT BIOLOGI KELAS XI IPS DI SMA NEGERI 1 TALIBURA - Jhon, Yoseph; Fitriah, Fitriah; Galis, Rofinus (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This study aims to determine the role of the Biology Teacher in Increasing Students' Interest in Learning at SMA Negeri 1 Talibura, Talibura District, Sikka Regency. This research was conducted from 13 February to 14 March 2023. The type of research used was a qualitative descriptive approach. The data collection method used consisted of data reduction, data presentation, and drawing conclusions.Based on the results of interviews and observations in the field, it can be concluded that the role of teachers with cross-interest in biology at SMA Negeri1Talibura and students' learning interest in subjects with cross-interest in biology at SMA Negeri 1 Talibura has increased